Dairy consumption and risk of esophagus cancer in the prostate, lung, colorectal, and ovarian cohort - Wang, Tingting; Zhu, Yi; Zheng, Yuanzhu; Cao, Yang; Xu, Qin; Wang, Xiangan; Hu, Wenli; Zhang, Yun (Frontiers in Nutrition, 2022)
Epidemiological studies provide limited information on the relationship between dairy consumption and the incidence of esophagus cancer (EC). We examined whether eating dairy foods is associated with a lower risk of EC in an American population. In our study, we analyzed data from the Prostate, Lung, Colorectal, and Ovarian (PLCO) cancer screening trial, which included 101,723 subjects. Dairy product consumption was assessed using a dietary history questionnaire. We used Cox regression and restricted cubic splines to assess whether dairy consumption is associated with EC incidence. A total of 154 EC cases were identified after a median follow-up of 12.2 years. After adjusting for confounders, we discovered no statistically significant correlation between total dairy product consumption and EC risk (HR with 95% CI for ≥ 1.79 servings/day vs. ≤ 0.6 servings/day: 0.83, 0.50–1.38; p for trend = 0.465). Additionally, no associations were found between EC risk and other dairy foods such as milk, yogurt, and cheese. In summary, we concluded that the findings of the PLCO cohort do not suggest dairy consumption reduces the risk of EC.